Development of Comic Strip Learning Media on Human Reproductive System Material in Class XI MA Madani Alauddin Pao-Pao - Daud, Syamsul; Zulkarnaim, Zulkarnaim; Hasanah, Ummul (Universitas Islam Negeri Walisongo Semarang, 2024)
This study aims to 1) determine the characteristics of comic strip learning media on human reproductive system material class XI at MA Madani Alauddin Pao-pao. 2) to know the level of validity of comic strip learning media on the material of human reproductive system class XI at MA Madani Alauddin Pao-pao. 3) to know the level of practicality of comic strip learning media on the material of human reproductive system class XI at MA Madani Alauddin Pao-pao. 4) to know the level of effectiveness of comic strip learning media on human reproductive system material in class XI at MA Madani Alauddin Pao-pao. This type of research is research and development by referring to the ADDIE model which has five stages, namely analyze, design, develop, implement, evaluate. The research subjects were students of class XI MIA 1 at MA Madani Alauddin Pao-pao with a total of 33 people. The instruments used in this study were validation sheets, questionnaires and learning outcomes tests. The results of this study indicate that the comic strip developed has a level of validity with an average value of 3.67 with a very valid category. Then at the level of product practicality based on the results of the response questionnaire of educators and students obtained an average value of 88% with a very practical category. Furthermore, in the effectiveness test, the comic strips developed were included in the very effective category because the percentage of students' completeness was very high.